Integrated microbiome, transcriptome and metabolome insight into the alleviating mechanisms of sheep milk in a DSS-induced colitis mouse model - Wenna Yao; Ruilin Du; Shuo Yan; Teligun Bao; Huimin Zhang; Fang Yang; Yue Xue; Yulong Zhao; Siqin Bao; Xihe Li; Yongli Song (Journal of Functional Foods)
Inflammatory bowel disease (IBD) is a recurrent inflammatory disease affecting the gastrointestinal tract, including ulcerative colitis (UC) and Crohn's disease (CD). IBD mainly causes intestinal mucosal injury, intestinal flora and metabolite disturbance. An imbalance between pro-inflammatory and anti-inflammatory cytokines also is a hallmark of IBD. At present, IBD is treated with medicines. The latest studies have revealed the adverse effects of drugs on people's health. Numerous studies have shown that animal milk can effectively protect the intestinal mucosa and alleviate UC symptoms. It also exhibits antibacterial, antioxidant, anticancer and anti-inflammatory properties. Sheep milk (SM) contains a higher concentration of fatty acids, immunoglobulins, proteins, hormones, vitamins and minerals, which exhibits anti-inflammatory properties. The DSS-induced colitis mice are a chemically induced model that mimics UC-like pathology. However, it is unclear whether gut microbes and metabolites play a role in preventing and treating UC in sheep milk. In this study, 30 mice were randomly divided into 3 groups. Mice had free access to sheep milk for 14 days, and free access to 2.5 % DSS started on the 7th day of SM administration and sustained for 7 days. In this study, q-PCR, ELISA, IHC, microbiome, untargeted metabolome and transcriptome were employed to investigate the mechanisms of sheep milk treatment in colitis. ELISA and qPCR analysis showed that relative mRNA expression levels of TNF-α, IL-1β, IL-6, and IL-17 were decreased in SM treatment compared to DSS-induced colitis mice. In the DSS group, LGR5, KI67, and MUC2 were significantly lower than in the CON group, but the SM treatment increased these protein expression levels. We also found that the tight junction proteins expression level was elevated in the SM group compared to the DSS group. Microbiome analysis showed that potentially harmful genera, such as unidentified_Enterobacteriaceae and Romboutsia decreased. In contrast, beneficial genera, such as Alloprevotella and Muribaculum increased in the SM group compared to the DSS group. The KEGG of non-targeted metabolome analysis showed that these metabolites were involved in amino acid metabolism, such as phenylalanine metabolism and propanoate metabolism in the SM group compared to the DSS group. Heatmap analysis showed that the purine and tryptophan metabolism signaling pathways changed, especially kynurenic acid and indole-3-glycol aldehyde were significantly downregulated in the SM group compared to the DSS group. Transcriptome analysis demonstrated that the expression of genes related to the IL-17 signaling and PI3K-Akt signaling pathways, such as S100A8, S100A9, LNC2, CXCL3, CREB313, CREB314 and CHRM1 were downregulated in the SM group compared to the DSS group. The results suggest that sheep milk can effectively alleviate DSS-induced colitis via restoring gut microbes and metabolites and inhibiting IL-17 and PI3K-Akt signaling pathways, providing a potential dietary therapy for treating IBD.